Child mouthing of soil and presence of animals in child sleeping spaces are associated with growth faltering among young children in Dhaka, Bangladesh (CHoBI7 Program). Issue 8 (18th July 2020) - Monira, Shirajum; Bhuyian, Md. Sazzadul Islam; Parvin, Tahmina; Uddin, Ismat Minhaj; Zohura, Fatema; Hasan, M. Tasdik; Biswas, Shwapon K.; Hasan, Khaled; Masud, Jahed; Rashid, Mahamud‐ur; Rahman, Zillur; Papri, Nowshin; et al.
Abstract: Objective: The objective of the study was to investigate potential risk factors for growth faltering among children under 5 years of age. Method: We conducted a prospective cohort study of 553 children under 5 years from diarrhoea patient households in urban Dhaka, Bangladesh. Height and weight measurements were obtained at baseline and at a 12‐month follow‐up. Caregivers of young children were administered a monthly questionnaire on household sociodemographic characteristics and hygiene practices. Results: Children with caregiver reports of mouthing soil at the majority of household visits had a significant reduction in their height‐for‐age z ‐scores (HAZ) from baseline to the 12‐month follow‐up (ΔHAZ: −0.28 (95% confidence interval (CI): −0.51, −0.05)). A significant reduction in HAZ was also observed for children in households with animals in their sleeping space (ΔHAZ: −0.37 (95% CI: −0.71, −0.04)). Conclusion: These findings provide further evidence to support the hypothesis that child mouthing of soil and the presence of animals in the child's sleeping space are potential risk factors for growth faltering among young children. Interventions are urgently needed to provide clean play and sleeping spaces for young children to reduce exposure to faecal pathogens through child mouthing. Abstract : Objectif: L'objectif de l'étude était d'examiner les facteurs de risque potentiels de retard de croissance chez les enfants de moins de 5 ans. Méthode: Nous avons mené une étude de cohorte prospective sur 553 enfants de moins de 5 ans provenant de ménages avec des patients diarrhéiques dans la ville de Dhaka, au Bangladesh. Les mesures de taille et de poids ont été obtenues au départ et à 12 mois de suivi. Les personnes s'occupant de jeunes enfants (les gardiens) ont reçu un questionnaire mensuel sur les caractéristiques sociodémographiques des ménages et les pratiques d'hygiène. Résultats: Les enfants pour lesquels les gardiens ont déclaré qu'ils mâchouillaient de la terre lors de la majorité des visites à domicile présentaient une diminution du score Z de taille pour l'âge (TAZ) de manière significative de l'âge de référence au 12 mois de suivi (ΔTAZ −0, 28 (intervalle de confiance (IC) à 95%: −0, 51, −0, 05)). Une réduction significative des TAZ a également été observée pour les enfants des ménages ayant des animaux dans leur espace de couchage (ΔTAZ −0, 37 (IC95%: −0, 71, −0, 04)). Conclusion: Ces résultats apportent des données supplémentaires pour appuyer l'hypothèse selon laquelle le fait que l'enfant mâchouille de la terre et la présence d'animaux dans son espace de couchage sont des facteurs de risque potentiels de retard de croissance chez les jeunes enfants. Des interventions sont urgemment nécessaires pour fournir des espaces de jeu et de sommeil sains aux jeunes enfants afin de réduire l'exposition aux agents pathogènes fécaux par le mâchouillement des enfants.